2005
DOI: 10.1136/adc.2004.064964
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of amplitude integrated electroencephalographic background patterns within 24 hours of perinatal asphyxia

Abstract: Objective: To assess the time course of recovery of severely abnormal initial amplitude integrated electroencephalographic (aEEG) patterns (flat trace (FT), continuous low voltage (CLV), or burst suppression (BS)) in full term asphyxiated neonates, in relation to other neurophysiological and neuroimaging findings and neurodevelopmental outcome. Methods: A total of 190 aEEGs of full term infants were reviewed. The neonates were admitted within 6 hours of birth to the neonatal intensive care unit because of peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 30 publications
8
85
0
1
Order By: Relevance
“…These findings are consistent with studies in term infants that have highlighted that initially abnormal amplitude-integrated EEG patterns shortly after birth sometimes recover to normal within 24 h (7,8). The specific mechanisms of this early transient suppression are unclear.…”
Section: Articlessupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with studies in term infants that have highlighted that initially abnormal amplitude-integrated EEG patterns shortly after birth sometimes recover to normal within 24 h (7,8). The specific mechanisms of this early transient suppression are unclear.…”
Section: Articlessupporting
confidence: 81%
“…Amplitude-integrated EEG is an easily applied bedside technology that at term can be used to identify high-risk infants after neonatal hypoxia-ischemia (4). However, there is increasing evidence that abnormal patterns may be associated with rather variable outcomes (5,6) and that initially abnormal amplitude-integrated EEG patterns shortly after birth can recover to normal within 24 h (7,8). The mechanism of this rapid recovery is unclear.…”
mentioning
confidence: 99%
“…Spontaneous recovery of severely abnormal EEG patterns within 24 h in asphyxiated term infants is not uncommon. 10,11 Both positive and negative predictive values of an abnormal aEEG background pattern for subsequent poor neurodevelopmental outcome change significantly, even when assessed at different times (3 and 6 h) during the first 6 h of life. 12 Since the period from birth to the initial aEEG varied little in the study infants, the stage of evolution of damage would mainly be influenced by the timing of intrauterine hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…19 The duration of monitoring may be important as well, as several studies advocate longer monitoring beyond 24 h. A retrospective study in 2004 indicated that recovery of the background pattern to normal is not uncommon, and that the sooner the background pattern normalized, the better the prognosis. 20 Similarly, van Rooij et al 21 showed that in infants with severely abnormal patterns at 6 h, recovery to normal by 24 h resulted in mild or no disability in 61% of infants. Sleep-wake cycling (SWC) can also be used to determine prognosis in term infants with HIE, and is characterized as regular variations in aEEG bandwidth (Figure 2).…”
Section: Introductionmentioning
confidence: 99%